Ultrafast electron injection, hole transfer, and charge recombination dynamics in cdse QD super-sensitized Re(I)-polypyridyl complexes with catechol and resorcinol moiety: effect of coupling - Debnath, Tushar; Maity, Partha; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry C, 2015)
Ultrafast charge-transfer dynamics have been demonstrated in CdSe quantum dots (QD) using two Re(I)-polypyridyl complexes having pendent catechol (Re1,2) and resorcinol (Re1,3) as the sensitizer molecules. The energy level diagram of CdSe QD and Re1,2 and Re1,3 sensitizer reveals that photoexcited hole of CdSe QD can be transferred to both Re1,2 and Re1,3 molecule, and photoexcited Re1,2 and Re1,3 can inject electron in the conduction band, which has been confirmed by steady-state and time-resolved photoluminescence studies with selective photoexcitation. Femtosecond transient absorption studies have been carried out to monitor charge-transfer dynamics in early time scale. Transient absorption spectra show formation of cation radicals for both Re1,2 and Re1,3 in the 550-650 nm region with a peak at 590 nm region and broad absorption in the 650-1000 nm region, which can be attributed to photoexcited electron in the conduction band of CdSe QD. Charge recombination was determined by monitoring the decay of cation radicals as well as decay of an electron and found to be slower in the Re1,3/CdSe system as compared to that of the Re1,2/CdSe system, which is due to weaker electronic coupling in the former system.